Generation of thermal scattering libraries for liquids beyond the Gaussian approximation using molecular dynamics and NJOY/LEAPR - Marquez Damian, Jose Ignacio (2016)
In this paper we review the existing methodologies for the generation of thermal scattering libraries for liquids from molecular dynamics simulations, either by Fourier transform or developing models in the Gaussian approximation. To overcome the limitations of the Gaussian approximation in the quasielastic range, we present a modification introduced to the LEAPR module of NJOY to include a random jump diffusion model, and a methodology to obtain the required parameters. This methodology is applied to light water with good results.